n-ary Star Product: Construction and Integral Representation - HOUNKONNOU, MAHOUTON NORBERT; OUSMANE SAMARY, DINE (My University, 2013)
This paper addresses a construction of an n-ary star product. Relevant identities are given. Besides, the formalism is illustrated by a computation of eigenvalues and eigenfunctions for a physical system of coupled oscillators in an n-dimensional phase space.
Keywords: n-ary star product; integral representation; Schwartz space.